Re-Envisioning Islamic Scholarship: Maqasid Methodology as A New Approach: A Book Review - Abdullah, Ahmad Badri (Journal of Contemporary Maqasid Studies, 2023)
Professor Jasser Auda’s work entitled Re-envisioning Islamic scholarship: Maqasid Methodology as a New Approach, published in 2022 is arguably one of the most innovative approaches in contemporary Islamic scholarship and, in my personal opinion, it somehow contributes significantly and uniquely to the project of Islamisation of knowledge or, as some have termed it, knowledge integration. In this work, Auda arguably has managed to lay the foundation for knowledge integration in the form of a unified scheme which combines both a deep and holistic understanding of the revelation and the reality.